Squamous and Respiratory Metaplasia After Olfactory Mucosal Resection - Mori, Eri; Ueha, Rumi; Kondo, Kenji; Funada, Shotaro; Shimmura, Hajime; Kanemoto, Kai; Tanaka, Hirotaka; Nishijima, Hironobu; Otori, Nobuyoshi; Yamasoba, Tatsuya; Kojima, Hiromi (Frontiers in Neuroscience, 2021)
Resection of the olfactory mucosa (OM) is sometimes unavoidable during surgery; however, it is not known whether the OM can completely recover thereafter. The aim of this study was to uncover whether the OM fully recovers after mucosal resection and describe the process of OM regeneration. Eight-week-old male Sprague–Dawley rats (n = 18) were subjected to OM resection at the nasal septum (NS); six rats were euthanized for histological examination 0, 30, and 90 days after surgery. Immunohistochemistry was performed to identify olfactory receptor neuron (ORN) lineage cells [mature and immature ORNs and ORN progenitors, and olfactory ensheathing cells (OECs)], as well as dividing and apoptotic cells. Squamous and respiratory metaplasia and inflammatory cell infiltration were also assessed. On day 30 after resection, the mucosa had regenerated, and mainly contained thin nerve bundles, basal cells, and immature ORNs, with a few mature ORNs and OECs. On day 90, the repaired nasal mucosa had degenerated into stratified squamous or ciliated pseudostratified columnar epithelia, with reducing ORNs. The lamina propria contained numerous macrophages. Partial regeneration was observed within 1 month after OM resection, whereas subsequent degeneration into squamous and respiratory epithelia occurred within 3 months. Given the poor persistence of ORNs and OECs, OM resection is likely to result in olfactory impairment. Overall, surgeons should be cautious not to injure the OM during surgery.